Validation of the Brugia Test Plus to detect IgG4 antibodies in individuals from Belitung Timur, a Brugia malayi endemic area in Indonesia. - Taniawati Supali; Elisa Iskandar; Noviani Sugianto; Yenny Djuardi; Katherine Gass; Jean M Saunders; Peter U Fischer; Marco A Biamonte (PLoS Neglected Tropical Diseases)
The Brugia Test Plus (BT+) is a new rapid diagnostic test for Brugia species which detects human IgG4 antibodies specific for the immunogenic Brugia protein BmR1. The aim of this study was to evaluate the BT+ assay with several types of sample-matrices: whole blood, plasma, and dried blood spots (DBS) from individuals living in Belitung Timur, a Brugia malayi endemic area in Indonesia. Night blood was collected from residents living in four presumed endemic villages, while DBS were collected from schoolchildren living in those four villages. The sensitivity of BT+ was measured by comparing the BT+ results to microscopic examination for microfilaria (Mf). The sensitivity of BT+ with whole blood under field conditions was 84.9% (95% CI 68.1-94.9, n = 33), and with EDTA plasma under laboratory conditions was 95.9% (95% CI 88.5-99.1, n = 73). Specificity was not assessed as it is impossible do so for an antibody test in endemic areas. In Mf-negative individuals, BT+ detected IgG4 antibodies in 204 out of 1,547 adult plasma samples (13.2%) and 7 out of 146 plasma samples collected from children aged 10-16 (4.8%). Detection of IgG4 antibodies in DBS collected from first and second grade schoolchildren (age 6-8) showed that only 1 out of 244 schoolchildren was positive (0.1%). Three individual readers were responsible for reading the BT+ . Statistical analysis showed high agreement among those readers (Kappa agreement value above 0.9). Laboratory technicians found the BT+ is simple to perform, easy to interpret the results, and appreciated the small volume of blood required (5 µL). This study has demonstrated that the novel BT+ is feasible for teams to implement and achieves good sensitivity, making it well suited for monitoring and evaluating the progress of the brugian- filariasis elimination program.